Comparison of Hindlimb Conformation in Cats with and without Medial Patellar Luxation - Beer, Andrew James Carey; Langley-Hobbs, Sorrel; Belch, Alex (Veterinary and Comparative Orthopaedics and Traumatology, 2022)
Objectives Medial patellar luxation (MPL) is the most common developmental cause of hindlimb lameness in cats. The association between femoral and tibial conformation and MPL measured on computed tomography (CT) has not been reported in cats. The aims were to report femoral and tibial conformation in cats with and without MPL and to report normal femoral and tibial angles.Methods Angle of inclination of femoral neck (AI), anatomical lateral distal femoral angle (aLDFA), femoral trochanteric angle (FCT), angle of anteversion of femoral neck (AA), distal and proximal anteversion angle (DAA/PAA), overall tibial valgus (TV), tibial torsion (TT), tibial tuberosity displacement (TTD) and trochlear depth:patellar thickness ratio (T:P) were measured by three observers on CT of cats with and without MPL. Comparisons were made between groups. Inter-observer intraclass correlation coefficient (ICC) was calculated.Results Sixteen cats were recruited: eight control and eight with MPL. The aLDFA, PAA, TT, TTD and T:P were significantly less in cats with high-grade MPL. The AI, FCT, AA, DAA and TV were not significantly different. A high correlation was shown with inter-observer ICC in 33.33% and good correlation in 26.67% when comparing measurements between observers.Clinical Significance This study suggests that cats with high-grade MPL have decreased TT, TTD and T:P and may require tibial tuberosity transposition and femoral trochleoplasty. The PAA, TT and aLDFA were decreased, although clinical significance may vary and these cats may not require correctional osteotomies. Results should be interpreted with caution as high/good levels of inter-observer ICC occurred in less than two-thirds of cases between observers.
Keywords: computed tomography; corrective osteotomy; cat; patellar luxation; hindlimb conformation